2011
DOI: 10.2214/ajr.10.5403
|View full text |Cite
|
Sign up to set email alerts
|

Ossification Patterns of the Atlas Vertebra

Abstract: C1 ossification patterns and timing of synchondrosis fusion are variable. Knowledge of these patterns is important to better differentiate a normal variant from traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 11 publications
1
23
1
1
Order By: Relevance
“…21,22 A CT-based study found 16% incomplete fusion of the posterior synchondrosis in patients over age of 5 year. 23 A recent study reported the C1 morphology and ossification using fine CT images of temporal bone and sinus, and found a complete closure of the posterior synchondrosis in all patients at age of 3 years except for one subject at age of 4 years. 14 The present results showed the posterior synchondrosis closure at age of 4 years except for one subject with partly fusion at age of 8 years.…”
Section: Discussionmentioning
confidence: 95%
“…21,22 A CT-based study found 16% incomplete fusion of the posterior synchondrosis in patients over age of 5 year. 23 A recent study reported the C1 morphology and ossification using fine CT images of temporal bone and sinus, and found a complete closure of the posterior synchondrosis in all patients at age of 3 years except for one subject at age of 4 years. 14 The present results showed the posterior synchondrosis closure at age of 4 years except for one subject with partly fusion at age of 8 years.…”
Section: Discussionmentioning
confidence: 95%
“…As reported, the very first ossification centers in the spine appear at week 8 in the neural processes of upper cervical vertebrae, i.e., the atlas and axis, and consecutively progress caudad [11, 12]. To date, however, the evolution of linear, planar and spatial dimensions of the neural ossification centers has been established in detail using computed tomography and digital image analysis only for three typical vertebrae: C4 [4], T6 [28] and L3 [29].…”
Section: Introductionmentioning
confidence: 94%
“…The ossification process in cervical vertebrae is quite intricate and discussable [5, 11, 12, 1416]. There are three ossification centers per vertebra within cervical vertebrae C3–C7, one in its body and one in either neural arch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the atlas, three ossification centers were found: one located within the anterior arch and two located within the posterior arch. However, four ossification centers were found in the axis: one in the body, one in the dens and one in either neural arch [7, 13, 15, 17]. Because of flexion–extension at the atlantooccipital joint and rotation at the atlantoaxial joint, 3-dimensional sonographic evaluation of the atlas and axis in utero fetuses may frequently misjudge their malalignment or offset phenomena [12].…”
Section: Introductionmentioning
confidence: 99%